Pendampingan Komunitas Women Entrepreneur melalui Literasi Marketing Online di Jawa Barat - Ratnadewi; Novie Theresia Br. Pasaribu; Agus Prijon; Aan Darmawan Hangkawidjaj; Erwani Merry Sartika (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
The number of Indonesian women entrepreneurs is increasing, including women entrepreneurs in West Java. But the obstacles faced include not getting an education to do marketing; one solution is marketing using online media. This was overcome through online marketing literacy for women entrepreneurs, especially in West Java. Electrical Engineering Study Program, Universitas Kristen Maranatha in collaboration with the Women's Empowerment and Child Protection Office of West Java Province and Online partner has increased capacity in the form of online media use literacy. The method used was Participatory Action Research (PAR), namely participants were given lectures, training, practices, discussions, and questionnaires directly. The Participatory Action Research (PAR) is a step in a community or social group scientifically resolves their problem by conducting direction, improvement, and evaluating decisions on the steps they take. There are six steps in Participatory Action Research (PAR), namely critical reflection, critical dialectics, resource collaboration, risk awareness, plural structures, theory, practice, and transformation. From the results of the questionnaire, it was found that the participants' abilities improved from before the training. Participants felt that this workshop was very useful and useful, which was around 90%. This indicates that the workshop was successful and beneficial for the participants